Intercorrelation of Factors which Determine the Early Childhood Education Quality - Petrus Redy Partus Jaya; Felisitas Ndeot; Beata Palmin; Maria Fatima Mardina Angkur (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2023)
This research aims to describe the intercorrelation between various components of early childhood education (PAUD) quality. The PAUD quality components were reviewed based on the 8 National PAUD Standards (SNP-AUD). The study was conducted on 43 PAUD institutions in the districts of Manggarai, West Manggarai, and East Manggarai. Data were collected using a questionnaire consisting of 50 questions that covered various scopes of SNP-AUD. Each question's response was measured on a Likert scale and accompanied by a description of each level based on the substance of the instrument's statement. Data were analyzed using Path Analysis techniques. The study's results showed that the Teacher and Education Personnel standard was a significant determinant factor in determining children's growth and development, with a determinant coefficient of 83.7%. However, this factor's determination was not direct but through its correlation with other factors within the process component. Therefore, efforts to improve PAUD teacher qualifications, competencies, and quality need to be done simultaneously and comprehensively with various aspects that determine PAUD process quality, such as improving the ability to develop and design a contextual curriculum, improving pedagogical abilities and learning strategies, as well as improving the ability to accurately and meaningfully assess children's development.